2019
DOI: 10.26583/sv.11.3.07
|View full text |Cite
|
Sign up to set email alerts
|

Visualization of the interaction region of an oblique shock wave with a boundary layer by the radiation of a nanosecond surface sliding discharge

Abstract: The spatial structure of radiation of a surface sliding discharge with a duration of ~ 300 ns (plasma sheet) in inhomogeneous supersonic air flows including oblique shock wave in a discharge chamber of shock tube was experimentally investigated. The flows were created behind plane shock waves with Mach numbers 2.8-4.2; flow Mach numbers were 1.30-1.60. The flow in the discharge chamber included an oblique shock wave generated by the interaction of a supersonic flow with a small obstacle, and then reflected fro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(10 citation statements)
references
References 13 publications
0
10
0
Order By: Relevance
“…Analysis of high-speed imaging showed that the formation of a quasi-stationary flow occurs within 90-150 μs after the plane shock wave passes the obstacle. Its duration is about 150-500 μs, which corresponds to numerical simulation [15]. The total duration of a homogeneous co-current flow behind a plane shock wave is 180-650 μs depending on the Mach number of the initial shock wave (Fig.…”
Section: The Supersonic Flow In the Channel Around Obstaclementioning
confidence: 88%
See 4 more Smart Citations
“…Analysis of high-speed imaging showed that the formation of a quasi-stationary flow occurs within 90-150 μs after the plane shock wave passes the obstacle. Its duration is about 150-500 μs, which corresponds to numerical simulation [15]. The total duration of a homogeneous co-current flow behind a plane shock wave is 180-650 μs depending on the Mach number of the initial shock wave (Fig.…”
Section: The Supersonic Flow In the Channel Around Obstaclementioning
confidence: 88%
“…Therefore, in an inhomogeneous air flow with an oblique shock wave, a surface sliding discharge develops as a single channel located in a region of low density formed during the interaction of an oblique shock wave with the boundary layer (Fig. 5 c, d), [15]. In experimental photo images, the discharge channel looks like an intensively emitting band about 10 mm wide.…”
Section: Surface Sliding Discharge Characteristics In Supersonic Flowmentioning
confidence: 96%
See 3 more Smart Citations